Association between gastroesophageal reflux disease and coronary heart disease: A nationwide population-based analysis. Issue 27 (July 2016) - Chen, Chien-Hua; Lin, Cheng-Li; Kao, Chia-Hung
Abstract : Abstract: In this study, we aimed to determine the association between gastroesophageal reflux disease (GERD) and subsequent coronary heart disease (CHD) development, if any, and to evaluate whether longer use of proton pump inhibitors (PPIs) increases the risk of CHD. Patients diagnosed with GERD between 2000 and 2011 were identified as the study cohort (n = 12, 960). Patients without GERD were randomly selected from the general population, frequency-matched with the study group according to age, sex, and index year, and evaluated as the comparison cohort (n = 51, 840). Both cohorts were followed up until the end of 2011 to determine the incidence of CHD. The risk of CHD was evaluated in both groups by using Cox proportional hazards regression models. The GERD patients had a greater probability of CHD than the cohort without GERD did (log-rank test, P < 0.001 and 11.8 vs 6.5 per 1000 person-years). The GERD cohort had a higher risk of CHD than the comparison cohort did after adjustment for age, sex, hypertension, diabetes, hyperlipidemia, alcohol-related illness, stroke, chronic obstructive pulmonary disease, asthma, biliary stone, anxiety, depression, chronic kidney disease, and cirrhosis (adjusted hazard ratio [aHR]: 1.49, 95% confidence interval [CI]: 1.34–1.66). The risk of CHD was greater for the patients treated with PPIs for more than 1 year (aHR = 1.67, 95% CI = 1.34–2.08) than for those treated with PPIs for <1 year (aHR = 1.56, 95% CI = 1.39–1.74). Our population-based cohort study results indicate that GERD was associated with an increased risk of developing CHD, and that PPI use for more than 1 year might increase the risk of CHD.